The Impact of Covid-19 Pandemic on Maritime Connectivity - Prima Aris Wardhani; Abdul Rivai Ras; Yusnaldi Yusnaldi; Pujo Widodo; Herlina Juni Risma Saragih (CV. Rayyan Dwi Bharata, 2023)
Corona Virus Disease 2019 (Covid-19) is a large family of viruses that can cause a wide range of illnesses, from the common cold to catastrophic conditions such as MERS and SARS. From the beginning of its spread, all aspects of human life have been affected by the pandemic that has spread around the world, including the global economic downturn and decreased manufacturing capacity. In addition, this circumstance has a new impact on the dimensions of global sea trade. This study uses a descriptive qualitative research method. Through a descriptive qualitative approach, analyzing and obtaining conclusions is done by looking for theories from various sources of literature such as books, journals, articles or other media. The conclusions obtained from this study are Covid-19 has affected all forms of human activity, including trading activities by sea. The application of physical distancing on board merchant ships is one way to prevent the spread of Covid-19 during the voyage. After the Covid-19 pandemic, the trend of larger ship sizes and fewer ship companies has continued. The Covid-19 outbreak not only created a health emergency, but also shook the global economic sector. This has caused a sudden and dramatic reduction in global sea trade traffic and energy consumption.